ผู้นำการเปลี่ยนแปลงทางสังคมตาม หลักเศรษฐกิจพอเพียงของตำรวจในประเทศไทย - ทรงเจริญ วรรณมนัส (Journal of Human and Society, Sisaket Rajabhat University, 2022)
งานวิจัยนี้มีวัตถุประสงค์เพื่อศึกษาบริบทประเทศไทย บทบาทของผู้นำ การเปลี่ยนแปลงทางสังคม วิเคราะห์องค์ประกอบผู้นำการเปลี่ยนแปลงพร้อมกับข้อเสนอแนะเชิงนโยบายการพัฒนาบทบาทผู้นำ ใช้วิธีวิจัยด้วยการสังเกต การสัมภาษณ์ในกรณีศึกษา 7 คน ผลการวิจัยพบว่า บริบทของประเทศมีการปรับใช้หลักเศรษฐกิจพอเพียงและหลักพุทธธรรมแบบพึ่งพาตนเอง ทำให้เกิดดุลยภาพระหว่างมนุษย์กับธรรมชาติเพื่อนำไปสู่การพัฒนาอาศัยกระบวนการปฏิบัตินำร่องจนมีอิทธิพลต่อความศรัทธา และนำไปสู่ การเปลี่ยนแปลงความคิดของชาวบ้านด้วยคุณลักษณะ 4 ประการ ข้อเสนอเชิงนโยบายการพัฒนาบทบาทผู้นำการเปลี่ยนแปลงทางสังคมตามปรัชญาเศรษฐกิจพอเพียงของตำรวจในบริบทของภาคตะวันออกเฉียงเหนือของประเทศไทยได้ 6 นโยบาย 12 มาตรการ This research aimed to study contexts of Thailand, roles of leaders of social changes in the countries, and the leaders’ key elements. The social change agents were analyzed and introduced policy recommendations for leadership role development. The data was collected by observation and interview with the 7 social change leaders. The study results showed that the contexts involved living the principles of sufficiency economy and Buddhist self-reliance, which helped keeping the balance between nature and human needs, and eventually leading to sustainable development. Many pilot programs, with 4 key elements, had been conducted and influenced people thoughts and beliefs. In the end, 6 policies and 12 measures for leadership role development were introduced in accordance with the principle of sufficiency economy for police officers in the northeastern region of Thailand.